Penerapan Terapi Nesting Terhadap Perubahan Fisiologis Pada Bayi Berat Lahir Rendah di RSUD Wonogiri - Nova Eka Ramadhani; Maryatun Maryatun (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Background: Low Birth Weight (LBW) is the weight of the baby less than 2500 grams, LBW can occur due to gestational age which is less than the normal age of 37 weeks and the baby's weight is also lower from babies in general. Nonpharmacological efforts to improve or stabilizing the baby's physiology, one of which is Nesting Therapy which has not yet been done ever given. Objective: Describe the results of implementing therapy nesting on heart rate in low birth weight babies at Wonogiri Regional Hospital. Method: This application uses the case study method by conducting intervention on two LBW respondents. The instrument used is with Look at the physiological observation sheets for both respondents. Result: Once done application for 24 hours with a frequency of therapy for 3 days consecutively. Showing an increase in physiological in both respondents, by looking at the observation sheet. Conclusion: Nesting therapy is effective for increase the heart rate of low birth weight babies.